(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of this present study is to assess and compare the diagnostic accuracy of the Modified RIPASA Score and Alvarado Score in patients with suspected acute appendicitis. Study Design: cross-sectional comparative study. Place and Duration of Study: This study was conducted at the Department of Surgery, Central Park Teaching Hospital, Lahore from January 2023 to December 2023. Methods: As a part of the cross-sectional comparative research study was conducted on 300 participants who were exhibiting symptoms which were suggestive of acute appendicitis. Patients were selected on the bases of inclusion and exclusion criteria. Alvarado Score and Modified RIPASA Score were calculated for each one of the patients. Usually, the standard clinical practice was followed through diagnostic imaging like CT or ultrasound scans. The sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of the two scoring systems were calculated. Results: The details provided in research analysis included the sensitivity, specificity, positive predictive value, and negative predictive value, diagnostic accuracy of Modified RIPASA Score and Alvarado Score. Conclusion: The study tried to get information on the comparison of the diagnostic efficiency of the Modified RIPASA Score and Alvarado Score in acute appendicitis. It was found that sensitivity of both the systems was almost same, but specificity and accuracy of Modified RIPASA was more than Alvarado scoring system.